Founder effect of the Glu89Gln TTR mutation in the Bulgarian population. (2nd October 2019) - Kirov, Andrey; Sarafov, Stayko; Pavlova, Zornitza; Todorov, Tihomir; Chamova, Teodora; Gospodinova, Mariana; Tournev, Ivailo; Mitev, Vanyo; Todorova, Albena
Abstract: Hereditary transthyretin amyloidosis is an autosomal dominant genetic disorder caused by missense mutations in the TTR gene resulting in amyloid formation of the transthyretin protein. Depending on the system affection, the manifestations may be different and high heterogeneity in the penetrance is observed. An endemic region in Bulgaria exists where the TTR mutation Glu89Gln is found with high frequency. This is a rare mutation and was probably introduced in the population by a common ancestor. This phenomenon, called "founder effect" was proved in carrier families by haplotype analysis of microsatellite markers showing linkage disequilibrium. Allele frequencies were analyzed and haplotype reconstruction was done with Arlequin v.3.01 software. The common ancestry of the carriers was demonstrated using additional data for their genealogies and microsatellite data from a control group of non-affected individuals. The results show that the mutation Glu89Gln is linked to one haplotype, called "hypothetical founder haplotype" which was compared to published haplotype data from other European patients and no similarity was found. Further population genetics studies of carriers of the Glu89Gln mutation from other endemic regions are required in order to clarify the geographical distribution of the mutation.